2013
DOI: 10.1136/annrheumdis-2012-203023
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new exon 2-skipped TNFR1 transcript: regulation by three functional polymorphisms of the TNFR-associated periodic syndrome (TRAPS) gene

Abstract: Our study provides a new mechanism of TNFRSF1A regulation whereby three polymorphisms in the promoter, exon 1 and intron 4 have a functional and combined effect on exon 2 splicing, via a coupling mechanism between transcription and splicing. These polymorphisms may affect the phenotype of TRAPS and TRAPS-like patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Point mutations/variations are also known to cause alternative splicing. Rittore et al (2014) showed three variations [rs4149570(c.-610G > T), rs767455(c.36A > G,pPro12Pro), rs1800692(c.473-33C > T)] in the promoter, exon 1 and intron 2, respectively, of TNFRSF1A gene enhance the splicing of exon 2 in vitro . These variations appeared to have a role in the pathogenesis of TRAPS disease ( Rittore et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point mutations/variations are also known to cause alternative splicing. Rittore et al (2014) showed three variations [rs4149570(c.-610G > T), rs767455(c.36A > G,pPro12Pro), rs1800692(c.473-33C > T)] in the promoter, exon 1 and intron 2, respectively, of TNFRSF1A gene enhance the splicing of exon 2 in vitro . These variations appeared to have a role in the pathogenesis of TRAPS disease ( Rittore et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“… Rittore et al (2014) showed three variations [rs4149570(c.-610G > T), rs767455(c.36A > G,pPro12Pro), rs1800692(c.473-33C > T)] in the promoter, exon 1 and intron 2, respectively, of TNFRSF1A gene enhance the splicing of exon 2 in vitro . These variations appeared to have a role in the pathogenesis of TRAPS disease ( Rittore et al , 2014 ). Furthermore, in another study, Tone et al (2011) suggested that c.910G > A variant (rs75977701) leads to the skipping of MEFV exon 2.…”
Section: Discussionmentioning
confidence: 99%
“…Another detailed study described a TNFR1 transcript lacking exon 2 (TNFR1-d2) and its association with a specific haplotype at 3 single nucleotide polymorphisms (SNPs) previously associated with TNF-receptor-associated periodic syndrome (TRAPS). These SNPs have distant locations along the TNFR1A gene: rs4149570 lies at the promoter region (c.610G>T), rs767455 at exon 1 (c.36A>G) and rs1800692 at exon 4 (c.473-33C>T), so it is plausible that an interplay of transcription and splicing dynamics determines transcript outcome ( 16 ). This evidence strongly suggests that these SNPs disrupt splicing enhancers/silencers along intronic or exonic sequences, an aspect yet to be studied for other reported SNPs associated with TRAPS ( 17 ) or other inflammatory conditions, including Crohn's disease ( 18 ).…”
Section: Known Isoforms In Tnf Signalingmentioning
confidence: 99%
“…The demonstration by Rittore et al ( 16 ) that SNPs can have an effect on the alternative splicing pattern of the TNFR1 gene may be the cornerstone that joins two groups of association studies, namely, transcript diversity and SNPs, and sheds light on their association. The Rittore group identified that SNPs rs4149570, rs767455 and rs1800692 have a combined effect on the TNFR1 transcript output through regulation of alternative splicing.…”
Section: Splicing Potentialmentioning
confidence: 99%
“…[ 7 8 ] Some authors have also utilized the ultrasonography to predict the outcome after local steroid injection. [ 9 10 ] It has been demonstrated that the therapeutic success of local steroid injection is mainly associated with the finding of power Doppler signal. [ 9 ] The initial median nerve swelling and its ratio have also been presented as a predictor of response after steroid injection.…”
Section: Introductionmentioning
confidence: 99%